2004
DOI: 10.1083/jcb.200402153
|View full text |Cite
|
Sign up to set email alerts
|

Distinct molecular forms of β-catenin are targeted to adhesive or transcriptional complexes

Abstract: β-Catenin plays essential roles in both cell–cell adhesion and Wnt signal transduction, but what precisely controls β-catenin targeting to cadherin adhesive complexes, or T-cell factor (TCF)-transcriptional complexes is less well understood. We show that during Wnt signaling, a form of β-catenin is generated that binds TCF but not the cadherin cytoplasmic domain. The Wnt-stimulated, TCF-selective form is monomeric and is regulated by the COOH terminus of β-catenin, which selectively competes cadherin binding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
273
3
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 297 publications
(295 citation statements)
references
References 47 publications
(82 reference statements)
16
273
3
3
Order By: Relevance
“…This interaction was also observed using purified arm domain and CTD components followed by semiquantitative Western and blot overlay analysis (39). With similar methods, two studies found that the CTD of ␤-catenin could compete its binding to the cadherin (39,47), but not TCF (47), raising the possibility that in a full-length protein the CTD may fold back along the arm domain in a closed conformation that restricts binding to some partners (27,47). However, specific binding between the CTD and the arm domain was not supported when Coomassie-stained gels were employed to quantify binding (19) or NMR spectroscopy was used to detect transient weak interactions (29).…”
Section: Discussionmentioning
confidence: 99%
“…This interaction was also observed using purified arm domain and CTD components followed by semiquantitative Western and blot overlay analysis (39). With similar methods, two studies found that the CTD of ␤-catenin could compete its binding to the cadherin (39,47), but not TCF (47), raising the possibility that in a full-length protein the CTD may fold back along the arm domain in a closed conformation that restricts binding to some partners (27,47). However, specific binding between the CTD and the arm domain was not supported when Coomassie-stained gels were employed to quantify binding (19) or NMR spectroscopy was used to detect transient weak interactions (29).…”
Section: Discussionmentioning
confidence: 99%
“…44) does, however, suggest mechanisms by which phosphorylation at the Akt target site might participate in localization. The C-terminal portion of the protein, including R10, is implicated in the nuclear import and export of β-catenin 45 , and it is also suggested that conformational changes in this region help partition β-catenin between nuclear and membrane pools 46 . Phosphorylation of Ser552 may therefore modulate the translocation of β-catenin through nuclear pores or affect its conformation 47,48 .…”
Section: Wnt and Pten-akt Pathways Cooperate In Isc Activationmentioning
confidence: 99%
“…Participation of b-catenin in cell-cell adhesion or Wnt signaling is determined by competitive binding of b-catenin to a-catenin and the actin network versus Wnt signaling components in the cytoplasm (Gottardi and Gumbiner, 2004;Nelson and Nusse, 2004;Bienz, 2005;Gumbiner, 2005;Brembeck et al, 2006). Switching of b-catenin from cell adhesion to Wnt signaling can be induced by tyrosine phosphorylation of b-catenin, which promotes binding to BCL9-2 instead of a-catenin.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of E-cad during tumor progression could likewise promote Wnt signaling (Nelson and Nusse, 2004;Bienz, 2005). However, E-cad loss-of-function in tumor cells is not often associated with increased b-catenin signaling and specific contexts in which the cadherin-bound pool of b-catenin is released for signaling remain poorly understood (van de Wetering et al, 2001;Gottardi and Gumbiner, 2004;Nelson and Nusse, 2004;Gumbiner, 2005).…”
Section: Introductionmentioning
confidence: 99%